2015
DOI: 10.1590/0100-5405/2068
|View full text |Cite
|
Sign up to set email alerts
|

Variação da sensibilidade de populações de Phakopsora pachyrhizi a fungicidas inibidores da desmetilação no Brasil

Abstract: Durante as safras 2008/09, 2009/10 e 2010/11 foi monitorada a sensibilidade do fungo Phakopsora pachyrhizi aos fungicidas tebuconazol, ciproconazol, metconazol e protioconazol (inibidores da desmetilação, IDMs). Folhas destacadas de soja foram tratadas com os fungicidas em doses variando de zero a 32 mg L-1 (tebuconazol, ciproconazol e metconazol) e zero a 8 mg L-1 (protioconazol) e inoculadas com esporos de P. pachyrhizi provenientes de lavouras de soja de diferentes regiões produtoras. As folhas inoculadas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
6
0
9
Order By: Relevance
“…agropec. bras., Brasília, v.51, n.5, p.407-421, maio 2016 DOI: 10.1590/S0100-204X2016000500002 fungi populations (Schmitz et al, 2014;Xavier et al, 2015).…”
Section: Fungicidesunclassified
“…agropec. bras., Brasília, v.51, n.5, p.407-421, maio 2016 DOI: 10.1590/S0100-204X2016000500002 fungi populations (Schmitz et al, 2014;Xavier et al, 2015).…”
Section: Fungicidesunclassified
“…The isolate from Caseiros-RS presented the lowest EC 50 value (0.20 mg L -1 ), while the Itaberá-SP isolate presented the highest value (1.64 mg L -1 ). XAVIER et al (2015) observed the EC 50 values between 0.000001 and 0.39 mg L -1 for isolates from eight Brazilian states. JULIATTI et al (2017) reported values between 0.0001 and 3.16 mg L -1 for isolates from Minas Gerais and Mato Grosso do Sul.…”
Section: Resultsmentioning
confidence: 90%
“…At that moment, Silva et al (2008) reported the control reduction in experiments, and later was confirmed by Reis and Deuner (Reis et al, 2015) in the P. pachyrhizi sensitivity reduction measured by the IC 50 . Later, Xavier et al (2015) demonstrated the presence of cross-resistance among DMIs.…”
Section: Figurementioning
confidence: 99%